Lega svečke v simetričnem zgorevalnem prostoru - Bizjan, Frančišek (Strojniški vestnik, 1999)
The spark plug in a small two stroke engine is often positioned in the middle of the cylinder head. The central position is comparatively favorable with respect to the activity in the cylinder, as well as from the technological point of view. Measurements of the flame front speed in a cylinder established that the flame does not spread symetrically with respect to the composition of the exhaust gas. Further, it was established that the change of the spark plug's position, or the addition of a second spark plug, results in a more favorable composition of the exhaust gasses without changing the characteristics of the engine. A duble outlet thyristor ignition system of high voltage with the possibility of adjusting the preignition during engine operation, was used. The results show that the central position of the spark plug is a low-priced solution which nowadays is not always acceptable.
Keywords: motorji ZNZ; motorji dvotaktni; prostor zgorevalni; svečke; dvotaktni motorji; izgorevanje